Encyclopedia of Islam and the Muslim world - Martin, Richard C. (New York : Macmillan Reference USA : Thomson/Gale, 2003)
"This two-volume set on Islam is a timely resource aimed at the general reader. More than 500 articles, 200-5,000 words in length, describe the Islamic world from its known beginnings to the present day. A 'Synoptic Outline of Entries' at the beginning of volume one presents a thematic overview of the encyclopedia that facilitates browsing. A glossary of terms and a pronunciation key appear at the end of volume two, followed by genealogies, timelines, and a detailed index."--"Reference that rocks," American Libraries, May 2005.
v. 1. A-L -- v. 2. M-Z, index.
Includes bibliographical references and index.
Keywords: Islam -- Encyclopedias